Synergistic effect of carbon nanomaterials on a cost-effective coral-like Si/rGO composite for lithium ion battery application - Benzait, Zineb; Yuca, Neslihan (Elsevier BV, 2020)
Abstract The emergence and the continuous rise of smart technologies require to emergently meet their ever-increasing energy demand. Improving the commercial lithium-ion batteries (LIB) by using silicon —which has a distinct energy storage capacity— might be a promising solution. However, solving Si-related problems, such as gross volume variation and low electrical conduction, is indispensable. Preparing different Si nanostructures having certain internal voids, and adding some conductive materials, are two smart approaches largely used to mitigate the volume expansion and to enhance the electrons transport of LIB anodes. Still, their raw materials and their preparation methods are generally costly, which limits their feasibility for commercial scalability. In this study, we synthesized a coral-like nanoporous Si/rGO composite, starting from cheap raw materials (graphite and Al–Si powders), and using simple methods which do not need any high temperatures or sophisticated equipment. The preparation steps were also reduced, as the reactions of Al-etching and GO reduction concurrently occurred. The LIB half-cells made on this composite were further improved by incorporating other carbon nanomaterials which had a synergistic effect on both cycling and rate performances: a reversible capacity of 1080 mAh g− 1 at 0.2 A g− 1 after 250 cycles; and ∼1710, 1300, 1030 and 840 mAh g− 1 at a rate of 1, 2, 3, and 4 A g− 1 respectively, have been achieved. Testing a full battery with an LCO cathode has also given a promising result: a reversible capacity of ∼54 mAh g− 1 at 36 mA g− 1 after 25 cycles has been obtained.
Keywords: Silicon anode; Synergistic effect; Carbon nanomaterials; Graphene; Lithium ion battery